DETECTION OF ADVERSARIAL ATTACKS USING HYBRID GENERATIVE ADVERSARIAL NETWORKS (GANS) - K.Bala Bhaskar; Dr.R.Satya Prasad (Revista Electronica de Veterinaria, 2024)
Adversarial attacks are a common technique used in machine learning to find vulnerabilities in deep learning models. In the context of hybridgenerative adversarial networks (GANs), adversarial attacks are used to perturb the input data so that the generated outputs are manipulated to produce unexpected or undesirable results. One example of an adversarial attack in GANs is the "Fast Gradient Sign Method" (FGSM), which involves adding a small perturbation to the input data to cause the GAN to generate an output that is significantly different from the desired result. This technique is often used to test the robustness of GANs against attacks and to identify potential weaknesses that malicious actors could exploit. Another type of adversarial attack in GANs is known as the "Boundary Attack," which involves finding the boundary between the decision regions of the generator and the discriminator in order to identify inputs that can be manipulated to produce a desired output. This paper introduced a hybrid DL model to overcome various issues in existing models. Experiments are conducted on two datasets such as MNIST dataset. Overall, adversarial attacks in hybrid GANs are an essential area of research as they help to identify potential vulnerabilities in the models and enable researchers to develop more robust and secure machine learning systems.